Museum as geopolitical entity: Toward soft combat. Issue 6 (6th May 2022) - Miller, Jacob C.; Wilson, Sharon
Abstract: Many scholars have examined the museum as a site of politics. This paper reviews recent research on museums and puts forward "soft combat" as a device for understanding how museums operate as geopolitical entities today. Soft combat includes (a) enrolling the visitor in affective atmospheres, (b) engaging with violence and trauma, and (c) embodied persuasion. We examine a military museum in the U.S.A to substantiate soft combat as a kind of biopolitics.